2018
DOI: 10.1038/s41398-018-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic itch

Abstract: Psychogenic itch can be defined as “an itch disorder where itch is at the center of the symptomatology and where psychological factors play an evident role in the triggering, intensity, aggravation, or persistence of the pruritus.” The disorder is poorly known by both psychiatrists and dermatologists and this review summarizes data on psychogenic itch. Because differential diagnosis is difficult, the frequency is poorly known. The burden is huge for people suffering from this disorder but a management associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
0
32
0
4
Order By: Relevance
“…In light of the above-mentioned points, we cannot exclude the possibility that the patient’s psychological stress could have had an influence on the subjective perception of pruritus, worsening it. However, we believe that in the case of our patient, the role of stress in exacerbating her symptoms was limited, and an alternative diagnosis, such as psychogenic itch, is extremely unlikely [ 31 ]. The patient did not have any personal or family history of mental illness, and the screening questionnaire performed during the follow up period for major depressive disorder showed only borderline results [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the above-mentioned points, we cannot exclude the possibility that the patient’s psychological stress could have had an influence on the subjective perception of pruritus, worsening it. However, we believe that in the case of our patient, the role of stress in exacerbating her symptoms was limited, and an alternative diagnosis, such as psychogenic itch, is extremely unlikely [ 31 ]. The patient did not have any personal or family history of mental illness, and the screening questionnaire performed during the follow up period for major depressive disorder showed only borderline results [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the patient experienced psychogenic itch. According to Misery et al,5 patients who scored higher on depression measures reported higher degrees of pruritus when compared to those who were not depressed.…”
Section: Discussionmentioning
confidence: 99%
“…É caracterizado na literatura como o ato de coçar a pele sem haver qualquer alteração e etiologia presentes [13]. Pode ser agravado ou desencadeado pelo estresse, ocorrendo uma liberação direta de neurotransmissores inflamatórios pelo sistema nervoso central [15]. O ato de arrancar cabelos repetitivamente (tricotilomania), apesar de ser considerado um dos transtornos compulsivos mais comuns por Gieler et al [16], teve uma frequência de 5% no estudo, sendo estimado como baixo em relação às outras DP já relatadas.…”
Section: I S C U S S ã Ounclassified